Role of the Basal Ganglia in Balance Control - Jasper E. Visser; Bastiaan R. Bloem (Neural Plasticity)
In this review paper, we summarize the important contributions of the basal ganglia to the regulation of postural control. After a brief overview of basal ganglia circuitries, the emphasis is on clinical observations in patients with focal lesions in parts of the basal ganglia, as the impairments seen here can serve to highlight the normal functions of the basal ganglia nuclei in postural control. Two particularly relevant functions are discussed in detail: first, the contribution of the basal ganglia to flexibility and to gaining control of balancecorrecting responses, including the ability to lend priority to the elements of a postural task; and second, processing afferent information by the basal ganglia, which is increasingly recognized as being highly relevant for postural control.